Influence of corporate social responsibility activities on financial performance of commercial banks in Meru town, Meru County - Karuti, Jephitha Kirimi (Meru: Jephitha Karimi Karuti, 2015)
There has been an increased and contained expenditure by a number of corporate organizations on activities that relate to corporate social responsibility (CSR) over the years globally. It is now accepted and expected that a profit- making organization must engage in socially responsive activities.The study examined CSR activities;education support, environmental conservation and infrastructure development which influence financial performance of commercial banks in Meru town Meru County. The study employed descriptive research design. The population of the study comprised of 212 staff of the 17 commercial banks that were selected using stratified random sampling method.Questionnaires for the commercial bank staff was the primary method of data collection. The instrument were piloted from the commercial banks Makutano which were included in the study sample. Data collected was analysed through the use of SPSS (Statistical Package for the Social Science) version 20.0 and then presented in frequencies and percentages in tables and charts. By the aid of descriptive and correlations designs data was analysed to deduce relationships. The findings indicated that CRS activities had a significant influence on financial performance with education support activities having the greatest influence. The alternative hypotheses were accepted. Since the study recommended that CSR activities can be generalized to the other financial institutions like SACCOs and micro-finances.
Includes Appendix and Reference.